2010
DOI: 10.4065/mcp.2009.0492
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Study of Musculoskeletal Pain Among Patients Receiving Bisphosphonate Therapy

Abstract: Mayo Clinic Proceedings 85 (2010) 341-348. doi:10.4065/mcp.2009.0492Received by publisher: 0000-01-01Harvest Date: 2016-01-04 12:20:30DOI: 10.4065/mcp.2009.0492Page Range: 341-34

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Caplan and colleagues [37] found an association of BP exposure and MSKP (RR=1.22; 95% 1.04, 1.44). They also found that female sex, depression, anxiety, comorbidity score, and the presence of a rheumatic disease are associated with a greater risk of a diagnosis of diffuse MSKP.…”
Section: Musculoskeletal Painmentioning
confidence: 95%
See 1 more Smart Citation
“…Caplan and colleagues [37] found an association of BP exposure and MSKP (RR=1.22; 95% 1.04, 1.44). They also found that female sex, depression, anxiety, comorbidity score, and the presence of a rheumatic disease are associated with a greater risk of a diagnosis of diffuse MSKP.…”
Section: Musculoskeletal Painmentioning
confidence: 95%
“…They also found that female sex, depression, anxiety, comorbidity score, and the presence of a rheumatic disease are associated with a greater risk of a diagnosis of diffuse MSKP. In elderly patients at high risk of osteoporotic fractures, BP prescription does not appear to be associated with a statistically significant risk of subsequent MSKP diagnoses [37].…”
Section: Musculoskeletal Painmentioning
confidence: 99%
“…Bisphosphonates reduce vertebral fractures risk and increase BMD. Non-vertebral hip fractures are also effectively reduced by some of these bisphosphonates (Wynn, 2005;Caplan et al, 2010). Alendronate, being associated with increased BMD and fracture risk reduction, is extensively recommended as a drug for treatment of postmenopausal osteoporosis (Black et al, 2000).…”
Section: Bone Resorptive Agentsmentioning
confidence: 99%
“…[23] Not only is there no known pathophysiology or causal relationship for bisphosphonate-associated musculoskeletal pain, but also, bisphosphonate use has been shown to relieve bone pain. [23] Not only is there no known pathophysiology or causal relationship for bisphosphonate-associated musculoskeletal pain, but also, bisphosphonate use has been shown to relieve bone pain.…”
Section: Y and Atrial Fibrillation Are Unclearmentioning
confidence: 99%